2006
DOI: 10.1007/s00484-006-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

A time series analysis of the relationship of ambient temperature and common bacterial enteric infections in two Canadian provinces

Abstract: The incidence of enteric infections in the Canadian population varies seasonally, and may be expected to be change in response to global climate changes. To better understand any potential impact of warmer temperature on enteric infections in Canada, we investigated the relationship between ambient temperature and weekly reports of confirmed cases of three pathogens in Canada: Salmonella, pathogenic Escherichia coli and Campylobacter, between 1992 and 2000 in two Canadian provinces. We used generalized linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
129
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 12 publications
15
129
2
4
Order By: Relevance
“…Although empirical downscaling projections of climate change on a local level contain uncertainties relating to the results, they present a step forward towards the need for implementing adaptation measures now. The Canadian Study showed that, for Alberta, the log relative risk of Salmonella weekly case counts increased by 1.2% for every degree increase in weekly mean temperature [23]. In our Study under conditions of increasing maximum monthly mean temperature for 1°C, the salmonellosis incidence increase for 5.2% per month.…”
Section: Resultssupporting
confidence: 39%
“…Although empirical downscaling projections of climate change on a local level contain uncertainties relating to the results, they present a step forward towards the need for implementing adaptation measures now. The Canadian Study showed that, for Alberta, the log relative risk of Salmonella weekly case counts increased by 1.2% for every degree increase in weekly mean temperature [23]. In our Study under conditions of increasing maximum monthly mean temperature for 1°C, the salmonellosis incidence increase for 5.2% per month.…”
Section: Resultssupporting
confidence: 39%
“…However, there is little new evidence that climate change significantly alters the prevalence of these diseases. Several studies have confirmed and quantified the effects of temperature on common forms of food poisoning, such as salmonellosis (18)(19)(20). These studies show an approximately linear increase in reported cases for each degree increase in weekly temperature.…”
Section: Climate Change and Food Securitymentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9] Although there is evidence of an association between outdoor temperature and mortality rates, the interplay between the two remains only partially understood in Asia because of a lack of databases with comprehensive, comparable data for most urban communities in low-and middle-income settings. 10,11 Evidence from European and American cities suggests that when outdoor temperatures are unusually high, there is a rise in hospital admissions 10,[12][13][14][15] for respiratory ailments, renal diseases, 12 and infectious diseases (both vector-borne and foodborne) and cerebrovascular accidents, including subarachnoid haemorrhage 13 and transient ischaemic attacks. [16][17][18][19][20][21][22] The risk of admission appears to be higher among the critically ill, 23 the very young, the very old, people of low socioeconomic status, 24 people with pre-existing medical conditions, 12,16 health-care workers, pregnant women 25 and people who are institutionalized, live alone or have poor mobility.…”
Section: Introductionmentioning
confidence: 99%